Higher psycho-physiological refinement in world-class Norwegian athletes: brain measures of performance capacity - Harung, H. S.; Travis, F.; Pensgaard, A. M.; Boes, R.; Cook-Greuter, S.; Daley, K. (Scandinavian Journal of Medicine & Science in Sports, 2011)
This study tested the hypothesis that the degree of psycho-physiological development is related to performance level in world-class athletes. We compared physiological and psychological patterns of 33 Norwegian world-class athletes to patterns in 33 average performing athletes. The subjects were matched for gender, age, and type of sport. Electroencephalography activity was recorded to measure brain integration; skin conductance was recorded to measure habituation to a loud stimulus; and paper-and-pencil tests were given to assess self-development, moral development, and frequency of peak experiences. A factor analysis (varimax rotation) reduced the eight variables to three factors that together accounted for 65.3% of the total variance: (1) physiological integration - brain integration and habituation rates, (2) self- and moral development, and (3) peak experiences. A MANOVA conducted on the factor scores showed a significant main effect for the experimental group collapsing across the three factors (P<0.0001). Individual ANOVAs showed significantly higher values for development (P=0.021) and physiological integration (P<0.0001) factor scores for the world-class athletes. The above measures can be seen as different expressions of an underlying dimension - human development. These data support the concept that higher psycho-physiological growth underlies higher performance.